The Synergistic Effect of Open Innovation and Customer Participation on Innovation Performance: Absorptive Capacity as a Key Mediator (Case Study: MSEs SiBakul in Yogyakarta) - Feri Dhoni Saputro; Dessy Isfianadewi (International Journal of Economics, Business and Innovation Research, 2024)
This research investigates how open innovation and customer involvement affect innovation performance, with absorptive capacity serving as a mediating variable. A quantitative methodology was adopted, incorporating field research to analyse the causal relationships among these variables. The study focuses on food micro and small enterprises (MSEs) in Yogyakarta, selecting a sample through random purposive sampling. This sample consists of 155 MSEs that are part of the SiBakul network and operate within the food industry, chosen based on the minimum path coefficient requirements. Both primary and secondary data were gathered using a 5-point Likert scale questionnaire administered directly by the researcher. The findings reveal that open innovation and customer involvement significantly and positively affect innovation performance. Furthermore, through the mediation of absorptive capacity, these factors also exert a positive indirect impact on innovation performance. It should be noted that this study is confined to food MSEs affiliated with SiBakul, and results may vary in different sectors.